2012
DOI: 10.1128/jb.01099-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of a Neisseria meningitidis Capsule Null Locus Strain from the Clonal Complex of Sequence Type 198

Abstract: Neisseria meningitidis is a commensal and accidental pathogen exclusively of humans. Although the production of polysaccharide capsules is considered to be essential for meningococcal virulence, there have been reports of constitutively unencapsulated strains causing invasive meningococcal disease (IMD). Here we report the genome sequence of a capsule null locus (cnl) strain of sequence type 198 (ST-198), which is found in half of the reported cases of IMD caused by cnl meningococcal strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…S1 in the supplemental material). Prior literature has indicated that, out of cnl meningococcal strains, ST-198 isolates in particular have been able to cause invasive meningococcal disease, despite being unencapsulated (9). The presence of three such unusual isolates in our data set raises the possibility that urethritis is another manifestation of this clade's pathogenicity.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…S1 in the supplemental material). Prior literature has indicated that, out of cnl meningococcal strains, ST-198 isolates in particular have been able to cause invasive meningococcal disease, despite being unencapsulated (9). The presence of three such unusual isolates in our data set raises the possibility that urethritis is another manifestation of this clade's pathogenicity.…”
Section: Resultsmentioning
confidence: 70%
“…1) (13). Three of these isolates (excluding NmJPb05-3) belonged to the ST-198 clade; among the rare cases of unencapsulated N. meningitidis isolates associated with invasive disease, isolates from the ST-198 clade are frequently found (9). Isolates in the ST-198 clade also lacked region B (ctrE, ctrF) genes, whereas NmJPb05-3 possessed them.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the invasive isolates, only 35 The remainder of the isolates (n ϭ 58) had an incomplete cps locus, with 40% of the isolates missing ctrA. Thirty-nine (67%) of the 58 isolates were ctrA negative; of those, 32 isolates lacked capsule biosynthesis and capsule transport genes and thus were classified as capsule operon-null (cnl) isolates (83,84). Fifteen isolates had insertions bearing coding sequences from IS1301 (80)(81)(82), including nine in cssF (MnW) and three each in cssA (MnY) and csb (MnB).…”
Section: Genotypic Characterization By Wgsmentioning
confidence: 99%
“…Neisseria meningitidis Capsule Null Locus Strain, sequence accession CAJS01000001 through CAJS01000042 [47]…”
Section: Bacteriamentioning
confidence: 99%